FOREIGN BODY INCIDENCE IN PREGNANT COWS AND BUFFALOS - ALASADI , RAHI NAHI (The Iraqi Journal of Veterinary Medicine, 2022)
Clinical study for (105) pregnant and (32) buffalo suffering from reticulopertonitis which are operated for foreign body removal by rumenotomy in different pregnancy stages. Result shown that the late stage pregnancy is the highest inicdence and all operated animals had no any complications and some of them delivered normally after 10 - 16 hr. and other within few days, this indicate that rumenotomy could be done at any stage of pregnancy even within few hours before parturition.